The impact of geographic proximity between auditor and client on audit quality: empirical evidence from Australia - Sarkar, Hasina Farhana (Curtin University, 2016)
Auditing is an important aspect of corporate governance and analyses of several contemporary financial scandals have found that insufficient levels of independent audit for effective monitoring and assurance. Recently Choi et al (2012) reported that geographic proximity has a significant impact on auditor- client relationship in US. Based on a sample of 520 (Australian listed) firms per year spanning the period from 2010 to 2013 (giving a final sample of 2080), this study examines geographic proximity between the auditor and client effect on audit quality.